Умови збіжності майже скрізь згортки функції з дельтаподібним ядром до цієї функції - Бушев, Д.М.; Харкевич, Ю.I. (Український математичний журнал, 2015)
Установлены достаточные условия сходимости свертки функции с дельтаподобным ядром к этой функции, которые используются для построения подпространств решений дифференциальных уравнений и их систем, изометрических пространствам действительных функций. We establish sufficient conditions for the convergence of the convolution of a function with delta-shaped kernel to this function. These conditions are used for the construction of the subspaces of solutions of differential equations and systems of these equations isometric to the spaces of real functions.